THE KANGAROO MOTHER CARE METHOD: NA INTEGRATIVE LITERATURE REVIEW (Fiep Bulletin - online, 2014)
Objective: To analyze the scientific production published on Kangaroo Mother Care. Methods: we conducted a Integrative Literature Review. To effect it was made from bibliographic research indexed in the database of the Virtual Health Librar, and the descriptor Controlled Health Sciences used "Kangaroo Mother Care", identifying sources information from numerous bases of scientific and technical literature. 22 articles were identified, however, only 9 met the inclusion criteria. Results: All articles were published in national journals, most concentrated in 2010, 77.7 % were qualitative studies. In more direct studies to parents and health care professionals in more asserted its benefits, aspects that may impede their applicability or it provides opportunities as well as ways to implement it successfully. Conclusion: It is expected that the study will contribute to the achievement of future research on the subject, is to assist in the construction of knowledge put up as gaps in the literature, or to deepen knowledge already generated by professionals.
Keywords: Pregnancy; Premature Newborn; Kangaroo Mother Care